THE ADAPTATION AND IMPLEMENTATION OF SINGA BATAK CARVING INTO LATIN LETTER TYPEFACE - Inko Sakti Dewanto; Muhammad Yulhanri Alfath (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
Every region in Indonesia has strong art with its characteristics, one of which is wood carving. Local wisdom in each region saves the uniqueness of its patterns and forms so that carving art in Indonesia becomes rich in identity and valuable cultural expressions. Of the many carving arts, the Batak region is famous for its carving art in the form of a lion, which is often found in the traditional houses of the Batak Toba. The lion carving symbolizes the figure of a generous king. In addition, lion ornaments in the Batak community are also believed to be bad luck repellents, which are thick with magical symbolic values inherited from the ancestors. Unfortunately, along with the times and technology, the art of Singa Batak carving is now starting to be forgotten and less recognized, especially by the younger generation. So, this research and design was carried out, as an effort to make local cultural artifacts closer to the current generation, especially in the Batak community and North Sumatra region. The research generally used a qualitative approach, namely visual adaptation. The result is a Latin typeface “Gorga”, inspired by the Singa Batak carving with the concept of “firm and dynamic”, which has been tested, then implemented on several regional tourism promotional media to preserve Batak culture through modern visual expression. This typeface is expected to be a bridge that perpetuates and preserves the noble values of Batak culture to the current and future generations.